2021
DOI: 10.1097/md.0000000000027565
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of genetic variants of opioid-related genes on opioid-induced adverse effects in patients with lung cancer

Abstract: Despite the dramatic advancement of cancer chemotherapy and immunotherapy, the insufficient progress has been made in basic or translational research on personalization of opioid therapy. Predicting the effectiveness of opioid analgesic therapy and the risk of adverse effects prior to therapy are expected to enable safer and more appropriate opioid therapy for cancer patients. In this study, we compared the incidence of opioid-induced adverse effects between patients with different variants of the genes relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Reports regarding the protective effect of carriers of SNP rs1799971 A118G with the G allele support the results of a study that indicates a significantly lower risk of somnolence as an adverse effect of morphine treatment in G/G homozygous patients compared to carriers of the A allele (0% vs. 28.4%, p = 0.005) [25]. The fact that patients are more susceptible to the sedative effects of opioids, especially morphine in carriers of A118G OPRM1 SNP with the A allele, may be considered as a potential marker of high-risk groups for this adverse effect, given that Hajj et al [13] found an association between the presence of lower levels of cognitive function in carriers of A118G SNP A/G and A/A, and thus the use of opioids may result in cognitive and sedative impairment in this group, and consequently deterioration of QoL of palliative care patients [13].…”
Section: Effect Of Polymorphisms On the Adverse Effects Of Morphine I...mentioning
confidence: 58%
See 1 more Smart Citation
“…Reports regarding the protective effect of carriers of SNP rs1799971 A118G with the G allele support the results of a study that indicates a significantly lower risk of somnolence as an adverse effect of morphine treatment in G/G homozygous patients compared to carriers of the A allele (0% vs. 28.4%, p = 0.005) [25]. The fact that patients are more susceptible to the sedative effects of opioids, especially morphine in carriers of A118G OPRM1 SNP with the A allele, may be considered as a potential marker of high-risk groups for this adverse effect, given that Hajj et al [13] found an association between the presence of lower levels of cognitive function in carriers of A118G SNP A/G and A/A, and thus the use of opioids may result in cognitive and sedative impairment in this group, and consequently deterioration of QoL of palliative care patients [13].…”
Section: Effect Of Polymorphisms On the Adverse Effects Of Morphine I...mentioning
confidence: 58%
“…This SNP was an independent factor in the occurrence of adverse effects [31]. Tanaka et al [25] investigated the two most common SNPs associated with individual variability in response to morphine, namely OPRM1 A118G and COMT Val158Met, and their potential association with opioid-induced adverse effects. As with the OPRM1 A118G SNP, the polymorphism studied in COMT was also found to be a statistically significant risk factor for opioid-induced somnolence [25].…”
Section: Comtmentioning
confidence: 99%
“…The increasing noradrenaline concentration may have also an effect on the analgesic effects ( Valomon et al, 2014 ). A clinical study of cancer pain in Asian patients found that GG carriers require a greater intravenous morphine dosage than AA carriers ( Tanaka et al, 2021 ), with the lack of drug preventing or lowering opioid-induced somnolence ( Cargnin et al, 2014 ). We showed significant MAF differences of rs4633 (C>T) between The MED, AMR and EAS populations.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the demand for opioid analgesia is different among individuals, which is likely to lead to huge differences in individual adverse reactions to opioids. In recent years, studies have increasingly begun to focus on the correlation between SNP and adverse reactions to opioids [11], expecting to find a new way to clinically predict the occurrence or severity of adverse reactions in patients. Most of these pioneering studies are animal experiments or single-center, small-sample clinical studies, and the results of these studies are sometimes ambiguous or even conflicting due to the excessive factors influencing the adverse reactions to opioids.…”
Section: Introductionmentioning
confidence: 99%